Capillary electrophoresis of phytochemical substances - Leena Suntornsuk (2018)
Applications of capillary electrophoresis (CE) for analysis of phytochemical substances (e.g. flavonoids, alkaloids, terpenoids, phenolic acid, quinones and coumarins) are reviewed. For example, CE analysis of sixteen tea ingredients were achieved within 10 min with the good precision (RSDs% < 1% for intra-day and 2% for inter-day) and linearity (R2> 0.990). Quantitation of sanguinarine and chelerythrine, alkaloids from Sanguinaria canadensis L. or Macleaya cordata (Wild) Br. R. by CE showed excellent linearity (R2> 0.998), precision (RSD% = 1.8%) and detection limit (2.4-3.0 μM). Determination of antraquinone-1-sulphonate was also obtained by this technique with good linearity (R2> 0.9999), precision (RSD% = 2%) and detection limit (0.7 μg/ml). Results of CE analysis from several studies are comparable to those of high performance liquid chromatography (HPLC), but the former is more useful for complex mixture samples where the analysis demands higher resolving power. Advantages of CE are high efficiency, low cost, short analysis time and simplicity, whereas disadvantages include low sensitivity comparing to HPLC and limitation of the preparative scale. © 2002 Elsevier Science B.V. All rights reserved.